TEACHING PHRASEOLOGICAL UNITS RELATED TO MONEY AS METAPHORS THROUGH AWARENESS ACTIVITIES AND AI TOOLS - Polvanova Maxzuna Farxadovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study examines the teaching of money-related phraseological units as metaphors in EFL contexts. Such expressions are often difficult for learners due to their figurative meanings. The research investigates the effectiveness of awareness-raising activities combined with AI-supported tools, such as chatbots and language learning applications. Intermediate-level students participate in tasks including context analysis, matching exercises, and guided discussions. A mixed-method approach is used, incorporating pre- and post-tests, classroom observation, and student questionnaires. The findings are expected to demonstrate that integrating awareness activities with AI support enhances learners’ comprehension, engagement, and ability to use idiomatic expressions accurately in communication.